Optimal management of a renewable resource utilized by a population with taxation as a control variable - Dubey, Balram; Patra, Atasi (Nonlinear Analysis: Modelling and Control, 2013)
A dynamical model is proposed and analyzed to discuss the effect of population on a resource biomass by taking into account the crowding effect. It is assumed that the resource biomass, which has commercial importance, is subjected to harvesting. The harvesting effort is assumed to be a dynamical variable and taxation is being used as a control variable. The optimal harvesting policy is discussed using the Pontryagin’s maximum principle.
Keywords: renewable resource; harvesting effort; taxation; stability